2012
DOI: 10.1109/tro.2012.2204513
|View full text |Cite
|
Sign up to set email alerts
|

Active Vision During Coordinated Head/Eye Movements in a Humanoid Robot

Abstract: While looking at a point in the scene, humans continually perform smooth eye movements to compensate for involuntary head rotations. Since the optical nodal points of the eyes do not lie on the head rotation axes, this behavior yields useful 3-D information in the form of visual parallax. Here, we describe the replication of this behavior in a humanoid robot. We have developed a method for egocentric distance estimation based on the parallax that emerges during compensatory head/eye movements. This method was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The active scanning behavior can be naturally studied using a robotic implementation to explain its association with depth perception. Kuang et al (2012) replicated this behavior on a humanoid robot and observed that the parallax-based distance estimates emerge during compensatory head/eye movements to fixate on a target during self-motion. When the robot rotated its head at a constant speed, its eyes rotated in the opposite direction to position the fixation object at the center of the image.…”
Section: Visual Perceptionmentioning
confidence: 65%
“…The active scanning behavior can be naturally studied using a robotic implementation to explain its association with depth perception. Kuang et al (2012) replicated this behavior on a humanoid robot and observed that the parallax-based distance estimates emerge during compensatory head/eye movements to fixate on a target during self-motion. When the robot rotated its head at a constant speed, its eyes rotated in the opposite direction to position the fixation object at the center of the image.…”
Section: Visual Perceptionmentioning
confidence: 65%
“…The solution of equation (17) is given by (18), which is a cubic equation. Then, the result in equation (16) is the E 1 (ρ, ϕ) of the PANDA ring.…”
Section: Simulationmentioning
confidence: 99%
“…Humanoid robot has become the best robotic type in robotic technology, which there are required many components and related technologies. Robotic research and development has been the important issue of the world robotic society for years [15][16][17][18][19], where the main part of robotic components is the process for brain communication and commands. To obtain the realistic robotic brain and its functions, the brains signal and communications are required to manipulate and test [20][21][22][23][24], therefore, the searching of realized technique for brain signals remains.…”
Section: Introductionmentioning
confidence: 99%
“…These ideas from biology inspired earlier work in robotics for distance estimation based on the parallax produced by camera rotations [29] and compensatory head/eye movements [18]. In later works the concept is extended to depth estimation [1].…”
Section: Introductionmentioning
confidence: 99%